Chemical Vapor Deposition Growth of Linked Carbon Monolayers with Acetylenic Scaffoldings on Silver Foil. Issue 18 (2nd March 2017) - Liu, Rong; Gao, Xin; Zhou, Jingyuan; Xu, Hua; Li, Zhenzhu; Zhang, Shuqing; Xie, Ziqian; Zhang, Jin; Liu, Zhongfan
Abstract : Graphdiyne analogs, linked carbon monolayers with acetylenic scaffoldings, are fabricated by adopting low‐temperature chemical vapor deposition which provides a route for the synthesis of two‐dimensional carbon materials via molecular building blocks. The electrical conductivity of the as‐grown films can reach up to 6.72 S cm −1 . Moreover, the films show potential as promising substrates for fluorescence suppressing and Raman advancement.